Assessment of Abdominal Fat Graft to Repair Anterior Skull Base after Malignant Sinonasal Tumor Extirpation. (March 2016) - Fonmarty, David; Bastier, Pierre-Louis; Lechot, Amandine; Gimbert, Edouard; de Gabory, Ludovic
Objective: Adult abdominal fat, which is known to contain pluripotent stem cells, is frequently used to treat cerebrospinal fluid leak. The aim of this study was to assess the efficacy and reliability of abdominal fat graft to close large skull base defects after extirpation of malignant sinonasal tumors. Study Design: Case series with chart review performed between 2009 and 2014. Subjects and Methods: Twenty-nine cases were included of consecutive patients who were suffering from malignant sinonasal tumors, operated by an endoscopic endonasal approach with anterior skull base extirpation and surgically induced cerebrospinal fluid leak. Skull base was repaired by 1 layer of "en bloc" autologous fat graft used as a plug in the onlay position. Epidemiologic data, medical history, defect size, length of hospitalization, and morbidity were analyzed. Results: Radiotherapy was given pre- and postoperatively in 4 (13.8%) and 23 (79.3%) patients, respectively. Mean defect size was 4.47 ± 2.9 cm 2 (range, 0.24-9.1 cm 2 ). Mean operative time was 210 ± 86 minutes. Mean length of hospitalization was 8.6 ± 3.7 days and 4.9 ± 2 days in the intensive care unit. No lumbar drain was used in this study. There was 1 case of cerebrospinal fluid leak (3.5%) and 2 cases of meningitis (6.9%), which resolved after medical treatment. Mean follow-up was 17 ± 13 months (range, 3-53 months). Conclusion: Abdominal fat graft is a safe and reliable material to close the anterior skull base after extirpation of malignant sinonasal tumors.